(untitled) (Ameghiniana, 2014)
Reticularia notica Reed, 1927 and Leiorhynchus sp. nov.? from the Pituil Formation are described and figured. Both species belong to the Balakhonia peregrina-Geniculifera tenuicostata Zone of late Westphalian age.